Business Development Strategy Analysis Using SWOT and QSPM Methods at Charlie Hospital Demak - Intan Laiti Qonita; Muhammad Sholahuddin; Rini Kuswati (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study analyzes the business development strategy of Charlie Hospital Demak, a newly established private hospital operating since late 2024. The hospital faces early-stage challenges related to fluctuating patient visits and the need to build competitive positioning in a growing regional healthcare market.Methodology: Using a mixed-method approach (qualitative and quantiative), the research identifies internal and external strategic factors through the McKinsey 7S Framework, Porter’s Five Forces, and PESTEL analysis, formulates strategic alternatives using SWOT, and determines strategic priorities using the Quantitative Strategic Planning Matrix (QSPM).Results: Findings reveal key strengths in modern facilities, competent human resources, and a comprehensive service philosophy, while weaknesses include ineffective inter-unit communication and suboptimal service procedures. Opportunities arise from industrial zone development, national healthcare programs, and digitalization trends, whereas threats stem from emerging competitors, rising non-communicable diseases, and dynamic health regulations. The IE matrix places the hospital in the